Profil Kemiskinan Desa Kertijayan, Kabupaten Pekalongan - Aini, Yuningkhus Yandar; Esariti, Landung (Jurusan Perencanaan Wilayah dan Kota, 2024)
Kertijayan Village is one of the poorest villages that implements the program. Poverty Laboratory in 2018-2019. The Poverty Laboratory Program aims to alleviate poverty by increasing income from potential in the village and easing the burden of the community by distributing water, housing, schools and health assistance. The purpose of this article is to analyze the poverty profile of Kertijayan Village. The results of the analysis prove that the facilities available in Kertijayan Village are quite complete, but a waste water disposal installation is needed to be improved. Social characteristics that affect poverty in Kertijayan Village are the low level of education and the extended number of families. Furtehrmore,the economic profile of the Kertijayan is related to the the social profile, that is the low level of welfare is caused by the in adequate income eraned by the families. It is recommended that, the government needs to provide non-formal education in the form of training. In the Poverty Laboratory program, skills training has been provided, but it needs to be supported again with work and financial internships for community businesses.